2015
DOI: 10.1111/mec.13312
|View full text |Cite
|
Sign up to set email alerts
|

Variable light environments induce plastic spectral tuning by regional opsin coexpression in the African cichlid fish, Metriaclima zebra

Abstract: Critical behaviors such as predation and mate choice often depend on vision. Visual systems are sensitive to the spectrum of light in their environment, which can vary extensively both within and among habitats. Evolutionary changes in spectral sensitivity contribute to divergence and speciation. Spectral sensitivity of the retina is primarily determined by visual pigments, which are opsin proteins bound to a chromophore. We recently discovered that photoreceptors in different regions of the retina, which view… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
82
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(87 citation statements)
references
References 64 publications
5
82
0
Order By: Relevance
“…Thus coexpression in double cones is low in the dorsotemporal retina. To further characterize this infrequent dorsotemporal coexpression, we re-examined previously fixed retinal samples from two fish shown to have unusually high coexpression in the more dorsal and temporal regions (Dalton et al, 2014(Dalton et al, , 2015. This extended the five regions transected previously to more globally sample opsin expression across the entire retina, similarly to what we did for the single cones in the present study.…”
Section: Double Conessupporting
confidence: 51%
See 3 more Smart Citations
“…Thus coexpression in double cones is low in the dorsotemporal retina. To further characterize this infrequent dorsotemporal coexpression, we re-examined previously fixed retinal samples from two fish shown to have unusually high coexpression in the more dorsal and temporal regions (Dalton et al, 2014(Dalton et al, , 2015. This extended the five regions transected previously to more globally sample opsin expression across the entire retina, similarly to what we did for the single cones in the present study.…”
Section: Double Conessupporting
confidence: 51%
“…All fish were reared in the same light environment, which, compared with natural M. zebra habitat, is rich in long wavelength light and has no ultraviolet light (Dalton et al, 2015). Rearing and handling of fish were carried out in accordance with an approved IACUC protocol (University of Maryland R15-54).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Traditionally, color vision was thought to only vary across species, but recent work in several taxa has found that color vision can also vary across populations [e.g., bluefin killifish (Fuller et al 2004), cichlids , stickleback (Flamarique et al 2013), guppies and close relatives (Sandkam et al 2015a, b)] which can be due to both genetic variation and plasticity (Fuller et al 2005;O'Quin et al 2012;Ehlman et al 2015; reviewed in Carleton et al 2016). Several studies have recently shown that visual systems are plastic with respect to developmental stage, time of day, and lighting environment (Fuller and Claricoates 2011;Johnson et al 2013;Flamarique et al 2013;Dalton et al 2015;Ehlman et al 2015;Sakai et al 2016).…”
Section: Introductionmentioning
confidence: 99%